Higher Education and the COVID-19 Pandemic. Cross-national Perspectives on the Challenges and Management of Higher Education in Crisis Times - Fetter, Bálint (Afrika Tanulmányok / Hungarian Journal of African Studies, 2022)
Fetter Bálint a következő művet mutatta be: Higher Education and the COVID-19 Pandemic. Cross-national Perspectives on the Challenges and Management of Higher Education in Crisis Times. Edited by: Fulufhelo Netswera; Ayenachew A. Woldegiyorgis And Tatiana Karabchuk. Brill, 410 P.